Адаптивний енергоефективний алгоритм керування для перетворювачів частоти циркуляційного насоса системи мікроклімату пташника - Горобець, В. Г.; Троханяк, В. І.; Антипов, Є. О.; Богдан, Ю. О. (Енергетика і автоматика, 2017)
Adaptive energy-efficient control for frequency converters circulating pump microclimate aviary V. Gorobets, V. Trohanyak, I. Antypov, Y. Bogdan Topicality. The development of new technologies in the energy sector, the transition to a new level of energy facilities, including poultry complex ventilation systems, characterized by acceleration of growth rates of quantitative and qualitative indicators yields and improve the entire structure ptahovyrobnytstva. The purpose of research - development of adaptive control algorithm for frequency converters circulating pump microclimate poultry house. Determining the optimal location and choice of power equipment for a new energy efficient system microclimate poultry house. Results. Found approximation dependence, which describes the required water flow for cooling supply air in the summer until the outside temperature with an accuracy of 5% approximation. Found approximation function, which describes the required flow of water to heat incoming air in winter until the outside temperature with an accuracy of 5% approximation. Conclusions i prospects. The research on the development of electrical complex in the poultry house construction algorithms enable control using graphical dependencies. Using underground water wells for cooling supply air in poultry indoors using heat-energy recovery in summer and winter seasons graphs flow of water circulating in the system by using the pump, depending on the outdoor temperature. Depending on the cost of water, with magnetic valves will be administered in place heat exchangers offline. At a temperature of 23 0C must use three heat exchangers with a water flow of 2.5 m3/h., And from +35 0C to +40 0C - 6 with a flow of heat water from 57 to 108 m3/h. Implemented automatic control of electrical modernized complex using Mega 2560, which is a microcontroller board based on the ATmega 2560.